Effect of Educational Program on Knowledge, Attitude, and Willingness of Nursing Students for Hematopoietic Stem-Cell Donation - Kim, Miok (Int J Environ Res Public Health, 2019)
This study explored how an educational program on hematopoietic stem-cell donation (HSCD) affects the knowledge, attitude, and willingness for HSCD among nursing students. The subjects were the nursing students at a university in Korea: 43 in the experimental group and 42 in the control group. All subjects took a pre-test, and only the experimental group attended an educational program. Both the groups completed two post-tests. Variables of interest were knowledge, attitude, willingness, and registration ratio for HSCD. The educational program increased knowledge (F = 8.093, p < 0.001) and attitude (F = −6.422, p < 0.001) of the experiment group. After the program, the experimental group showed higher willingness for HSCD (χ(2) = 7.609, p = 0.006) and higher registration ratio for HSCD (χ (2)= 4.258, p = 0.039) compared to the control group. The educational programs for knowledge and attitude about HSCD will affect the students’ future nursing, and influence clients and their families toward positive perception on HSCD and organ donations.